2020
DOI: 10.3389/fimmu.2019.03082
|View full text |Cite
|
Sign up to set email alerts
|

Systemic β-Adrenergic Receptor Activation Augments the ex vivo Expansion and Anti-Tumor Activity of Vγ9Vδ2 T-Cells

Abstract: TCR-gamma delta (γδ) T-cells are considered important players in the graft-vs.-tumor effect following allogeneic hematopoietic cell transplantation (alloHCT) and have emerged as candidates for adoptive transfer immunotherapy in the treatment of both solid and hematological tumors. Systemic β-adrenergic receptor (β-AR) activation has been shown to mobilize TCR-γδ T-cells to the blood, potentially serving as an adjuvant for alloHCT and TCR-γδ T-cell therapy. We investigated if systemic β-AR activation, using acu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 52 publications
(63 reference statements)
1
41
0
2
Order By: Relevance
“…In a recent study, it was reported that systemic β-adrenergic receptor activation, which was accomplished by dynamic physical exercise, mobilized γδ T cells to the blood and significantly augmented their subsequent in vitro expansion capacity and cytotoxic antitumor activity. 164 A placebo-controlled crossover study applying adrenergic receptor inhibitors indicated that effects on the γδ T cell compartment were mediated by the β2—rather than the β1 adrenergic receptor. 164 …”
Section: How To Improve the In Vitro Expansion And Effector Activity mentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study, it was reported that systemic β-adrenergic receptor activation, which was accomplished by dynamic physical exercise, mobilized γδ T cells to the blood and significantly augmented their subsequent in vitro expansion capacity and cytotoxic antitumor activity. 164 A placebo-controlled crossover study applying adrenergic receptor inhibitors indicated that effects on the γδ T cell compartment were mediated by the β2—rather than the β1 adrenergic receptor. 164 …”
Section: How To Improve the In Vitro Expansion And Effector Activity mentioning
confidence: 99%
“… 164 A placebo-controlled crossover study applying adrenergic receptor inhibitors indicated that effects on the γδ T cell compartment were mediated by the β2—rather than the β1 adrenergic receptor. 164 …”
Section: How To Improve the In Vitro Expansion And Effector Activity mentioning
confidence: 99%
“…It is possible that the donor variability observed in this study, as well as others, could be accounted for by variability in the donors' lifestyles. Exercise immediately prior to PBMC isolation has been shown to increase the ex vivo expansion of γδ T cells (42). In this study, a donor's level of exercise was predictive of their γδ T cell expansion potential.…”
Section: Discussionmentioning
confidence: 81%
“…There is no definitive explanation of the mechanisms that underlie this findings: even though a series of preclinical data have been published on the matter [ 20 , 21 , 22 ], these studies have stopped in the preclinical phase, failing to have some form of validation in the clinical setting.…”
Section: Resultsmentioning
confidence: 99%